Pelatihan Pemanfaatan Media Sosial Daring Sebagai Alat Pemasaran Bagi Masyarakat Di Era Pandemi - Nisa, Jihan Solehatun; Putri, Dian Sukma Fitriani; Alfalathi, Siti Aminah (Jurnal Pendidikan Luar Sekolah, 2021)
Community education is considered to be one of the educations that can provide a way and solution for problems in public education services, especially for people who are not served by formal education. The purpose of this training is to find out about the current development of social media and the role of social media as product marketing to improve the community's economy, especially the women of Bukit Mekar Wangi, Tanah Sareal District, Bogor City. The implementation method in this service activity is in the form of skills training. In the skills training activity carried out in community service is Training on the Use of Online Social Media as a Marketing Tool for the Community of Bukit Mekar Wangi, Tanah Sareal District, Bogor City in the Pandemic Era held on Sunday, December 13, 2020. held at the Bumi Menteng Asri Community Reading Park . With the skills training on the Utilization of Online Social Media as a Marketing Tool for the Community of Bukit Mekar Wangi, Tanah Sareal District, Bogor City in the Pandemic Era has become a solution for the community in marketing household products and being able to open their own industry by entrepreneurial way of selling products so that they can increase income and improve the economy of the family and society because it is able to open business opportunities and create jobs. AbstrakBagi yang tidak terlayani oleh pendidikan formal, pendidikan masyarakat dianggap menjadi salah jalan keluar bagi permasalahan pendidikan kepada masyarakat.  Tujuan dari pelatihan ini untuk mengetahui perkembangan media sosial saat ini dan peranan media sosial sebagai pemasaran produk untuk meningkatkan perekonomian masyarakat terutama ibu-ibu Bukit Mekar Wangi Kecamatan Tanah Sareal, Kota Bogor. Metode berupa pelatihan pemanfaatan media sosial daring sebagai alat pemasaran. di lakukan di Taman Baca Masyarakat Perumahan Bumi Menteng Asri. Dengan adanya pelatihan keterampilan Pemanfaatan Media Sosial Daring Sebagai Alat Pemasaran Bagi Masyarakat Bukit Mekar Wangi Kecamatan Tanah Sareal, Kota Bogor Di Era Pandemi menjadi solusi bagi masyarakat dalam memasarkan produk rumah tangga dan mampu membuka industri sendiri dengan cara berwirausaha dari menjual produk sehingga dapat menambah penghasilan dan meningkatkan perekonomian keluarga serta masyarakat karena mampu membuka peluang usaha dan menciptakan lapangan pekerjaan.Community education is considered to be one of the educations that can provide a way and solution for problems in public education services, especially for people who are not served by formal education. The purpose of this training is to find out about the current development of social media and the role of social media as product marketing to improve the community's economy, especially the women of Bukit Mekar Wangi, Tanah Sareal District, Bogor City. The implementation method in this service activity is in the form of skills training. In the skills training activity carried out in community service is Training on the Use of Online Social Media as a Marketing Tool for the Community of Bukit Mekar Wangi, Tanah Sareal District, Bogor City in the Pandemic Era held on Sunday, December 13, 2020. held at the Bumi Menteng Asri Community Reading Park . With the skills training on the Utilization of Online Social Media as a Marketing Tool for the Community of Bukit Mekar Wangi, Tanah Sareal District, Bogor City in the Pandemic Era has become a solution for the community in marketing household products and being able to open their own industry by entrepreneurial way of selling products so that they can increase income and improve the economy of the family and society because it is able to open business opportunities and create jobs.Keywords: Public Education, Social Media, Product MarketingAbstrakBagi yang tidak terlayani oleh pendidikan formal, pendidikan masyarakat dianggap menjadi salah jalan keluar bagi permasalahan pendidikan kepada masyarakat.  Tujuan dari pelatihan ini untuk mengetahui perkembangan media sosial saat ini dan peranan media sosial sebagai pemasaran produk untuk meningkatkan perekonomian masyarakat terutama ibu-ibu Bukit Mekar Wangi Kecamatan Tanah Sareal, Kota Bogor. Metode berupa pelatihan pemanfaatan media sosial daring sebagai alat pemasaran. di lakukan di Taman Baca Masyarakat Perumahan Bumi Menteng Asri. Dengan adanya pelatihan keterampilan Pemanfaatan Media Sosial Daring Sebagai Alat Pemasaran Bagi Masyarakat Bukit Mekar Wangi Kecamatan Tanah Sareal, Kota Bogor Di Era Pandemi menjadi solusi bagi masyarakat dalam memasarkan produk rumah tangga dan mampu membuka industri sendiri dengan cara berwirausaha dari menjual produk sehingga dapat menambah penghasilan dan meningkatkan perekonomian keluarga serta masyarakat karena mampu membuka peluang usaha dan menciptakan lapangan pekerjaan.